PENGARUH IKLIM ORGANISASI, MOTIVASI KERJA, DAN EFIKASI DIRI TERHADAP KINERJA GURU SMA DI KECAMATAN PALMERAH JAKARTA BARAT - Yudisti Prayigo Permana; Surasni Surasni; Lili Nurlaili (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of Organizational Climate, Work Motivation, and Self-Efficacy on the Performance of Senior High School Teachers in the Palmerah District, West Jakarta. Teachers play a strategic role in determining the quality of education, making it essential to understand the factors that affect their performance. This research employed a quantitative approach using a survey method involving 126 teachers selected through proportional sampling. The research instrument was a Likert-scale questionnaire measuring four key variables: Organizational Climate (X₁), Work Motivation (X₂), Self-Efficacy (X₃), and Teacher Performance (Y). Data were analyzed using multiple linear regression through SPSS version 27. The findings reveal that all three independent variables significantly affect teacher performance, both partially and simultaneously. The coefficient of determination (R²) of 0.240 indicates that 24% of the variance in teacher performance is explained by these variables, while the remaining 76% is influenced by other external factors. The F-test result (F = 12.857; Sig. = 0.000) confirms the simultaneous effect, while the t-test results show significant partial effects from Organizational Climate (t = 4.178; Sig. = 0.000), Work Motivation (t = 4.340; Sig. = 0.000), and Self-Efficacy (t = 1.998; Sig. = 0.048). These results emphasize that teacher performance is shaped not only by individual competence but also by environmental and psychological factors.